American Joint Committee on Cancer and College of American Pathologists Regression Grade: A New Prognostic Factor in Rectal Cancer. Issue 1 (January 2015) - Mace, Adam G.; Pai, Rish K.; Stocchi, Luca; Kalady, Matthew F.
Abstract : BACKGROUND: The American Joint Committee on Cancer and the College of American Pathologists provide guidelines for reporting pathologic response to neoadjuvant treatment of rectal cancer. The clinical relevance of these tumor regression grading guidelines is undefined. OBJECTIVE: This study evaluates the prognostic significance of the American Joint Committee on Cancer/College of American Pathologists regression grading. DESIGN: This is a retrospective cohort study based on data from a prospectively maintained colorectal cancer database. The cohorts were defined by American Joint Committee on Cancer/College of American Pathologists tumor regression grade. SETTING: This study was performed at a single tertiary referral center. PATIENTS: Five hundred thirty-eight patients with primary rectal adenocarcinoma who underwent neoadjuvant therapy between 1992 and 2012 were identified. MAIN OUTCOME MEASURES: The primary outcome measures were overall and disease-free survival, cancer-specific mortality, and cumulative recurrence rate. RESULTS: Five hundred thirty-eight patients were included, 105 of whom (19.5%) were American Joint Committee on Cancer/College of American Pathologists grade 0, 153 patients (28.4%) were grade 1, 181 patients (33.6%) were grade 2, and 99 (18.4%) were grade 3. Kaplan-Meier analysis revealed that American Joint Committee on Cancer/College of American Pathologists grade was associated with significant differences in overall survival ( p < 0.001), disease-free survival ( p < 0.001), and cumulative recurrence ( p < 0.001). No local recurrences were observed in American Joint Committee on Cancer/College of American Pathologists grade 0 patients. Five-year overall survival rates were 89%, 74%, 63%, and 40% ( p < 0.001); 5-year disease-free survival rates were 85%, 64%, 54%, and 33% ( p < 0.001); and 5-year recurrence rates were 7%, 18%, 25%, and 33% ( p <0.001) for American Joint Committee on Cancer/College of American Pathologists grades 0, 1, 2, and 3. After adjusting for significant covariates, including pathologic stage, American Joint Committee on Cancer/College of American Pathologists grade remained an independent predictor of overall survival ( p < 0.001), disease-free survival ( p < 0.001), and cumulative recurrence ( p < 0.001) in Cox regression analyses. LIMITATIONS: This was a retrospective study. There was a low local recurrence rate in our population, limiting the sensitivity of recurrence analyses. CONCLUSIONS: This is the first study to delineate American Joint Committee on Cancer/College of American Pathologists regression grade as an independent oncologic prognostic factor. This information can be used in discussions with patients who have rectal cancer. Abstract : See related Editorial on p. 1